PDAM TIRTA MOEDAL’S MEDIA RELATIONS ACTIVITIES - Imron, Saiful; Naryoso, S.Sos, M.Si, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Background of this research are focuses on media relations activities of PDAM Tirta Moedal thatt only aimed for the journalists that are work together with PDAM Tirta Moedal, also there are possibilities of difference in point of view from public relations officer towards some good development attempts of media relations to the mass media. This research’s aims is to get knowing the activities of PDAM Tirta Moedal Public Relation’s media relations. This research uses qualitative descriptive method. Researchers collected data by conducting interviews with the PDAM Tirta Moedal’s Head of Sub Division Public Relations which can be used as a key informant because it has a close relationship with the object of research, as well as an interview with a journalist who have experience covering news in PDAM Tirta Moedal. Based on the research results, it can be conclude that to conduct media relations activities, Public Relations of PDAM Tirta Moedal is using the principle of understanding and serving the media, as well as building a reputation as a party that is open to the media. Media relations activities conducted by PDAM Tirta Moedal like media gatherings, press conferences, press releases, and press interviews. The existence of the harmonious relationship between PDAM Tirta Moedal’s Public Relations with the media will create a situation of mutual respect for one another.